2009
DOI: 10.4161/cc.8.20.9855
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of survivin expression affects chromosome alignment and spindle checkpoint in mouse oocyte meiotic maturation

Abstract: Survivin is a member of inhibitors of apoptosis proteins (IAPs), which have multiple regulatory functions in mitosis, but its roles in meiosis remain unknown. Here, we report its expression, localization and functions in mouse oocyte meiosis. Survivin displayed a maximal expression level in GV stage, and then gradually decreased from Pro-MI to MII stages. Immunofluorescent staining showed that survivin was restricted to the germinal vesicle, associated with centromeres from pro-metaphase I to metaphase I stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 35 publications
2
32
1
Order By: Relevance
“…To investigate the expression profiles of SUMO-1 and SUMO-2/3 modified proteins during mouse oocyte maturation, we performed immunoblot analysis with samples collected after mouse oocytes had been cultured for 0 h, 4 h, 8 h, 9.5 h and 12 h, corresponding to the GV, premetaphase I, metaphase I, anaphase I and MII stages respectively, as reported by us previously. [34][35][36] Distinct profiles of modified proteins were recognized by anti-SUMO-1 and anti-SUMO-2/3 monoclonal antibodies. We detected only two bands (up, band A; low, band B) which were seen between the 72 kDa and 55 kDa markers, using the anti-SUMO-1 antibody (Fig.…”
mentioning
confidence: 99%
“…To investigate the expression profiles of SUMO-1 and SUMO-2/3 modified proteins during mouse oocyte maturation, we performed immunoblot analysis with samples collected after mouse oocytes had been cultured for 0 h, 4 h, 8 h, 9.5 h and 12 h, corresponding to the GV, premetaphase I, metaphase I, anaphase I and MII stages respectively, as reported by us previously. [34][35][36] Distinct profiles of modified proteins were recognized by anti-SUMO-1 and anti-SUMO-2/3 monoclonal antibodies. We detected only two bands (up, band A; low, band B) which were seen between the 72 kDa and 55 kDa markers, using the anti-SUMO-1 antibody (Fig.…”
mentioning
confidence: 99%
“…By anaphase and telophase, survivin localises to the spindle midzone and midbody respectively. Moreover, a similar expression pattern is evident at metaphase II similar to that seen in metaphase I (Sun et al 2009, Wang et al 2011. Manipulation of survivin expression in mouse and rat oocytes has indicated that this IAP is necessary for correct chromosome alignment and regulation of meiotic cell cycle (Sun et al 2009, Wang et al 2011.…”
Section: Other Iaps In the Ovarymentioning
confidence: 55%
“…Furthermore, immunoreactivity for survivin in oocytes has been observed at all follicle stages, and this IAP has been shown to play a direct role in meiotic maturation. Studies investigating the intracellular localisation of survivin have shown localisation and expression intensity changes during oocyte meiotic stage progression (Sun et al 2009, Wang et al 2011. Initially, survivin is highly expressed in the germinal vesicle.…”
Section: Other Iaps In the Ovarymentioning
confidence: 99%
“…32,34 This result suggests that septins may be dispensable for cytokinesis of the first PBE in mouse oocytes. Therefore, our study and our previous report 49 suggests that cytokinesis of the first PBE in mouse oocytes may be differently regulated when compared to cytokinesis in mitosis.…”
Section: Discussionmentioning
confidence: 88%